Solve for y 3(y-1)=2(y+1)

Math
3(y-1)=2(y+1)
Simplify 3(y-1).
Tap for more steps…
Apply the distributive property.
3y+3⋅-1=2(y+1)
Multiply 3 by -1.
3y-3=2(y+1)
3y-3=2(y+1)
Simplify 2(y+1).
Tap for more steps…
Apply the distributive property.
3y-3=2y+2⋅1
Multiply 2 by 1.
3y-3=2y+2
3y-3=2y+2
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 2y from both sides of the equation.
3y-3-2y=2
Subtract 2y from 3y.
y-3=2
y-3=2
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 3 to both sides of the equation.
y=2+3
Add 2 and 3.
y=5
y=5
Solve for y 3(y-1)=2(y+1)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top